Implementasi Pojok Literasi Sebagai Strategi Penigkatan Literasi Siswa di Lingkungan SDN 1 Tongka Kalimantan Tengah - Nor Hayat; Sondra Swestyani; Tri Yani Oktavia; Dila Asmianur; Widia Astuti; Yandi Novia; M. Hilman Rahmantara (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This community service program was implemented to address the low literacy levels among students in remote areas of Central Kalimantan, specifically at SDN 1 Tongka, Gunung Timang District, North Barito Regency. The main objective of the program was to implement a literacy corner as a strategy to improve student literacy and create a sustainable literacy ecosystem in the school environment. The method used included participatory and adaptive approaches, applying the concept of a